Analisis Persepsi Nasabah Dalam Penggunaan Pembiayaan Produk Mikro Menggunakan Akad Murabahah Studi Kasus BSI KCP Medan Kampung Baru - Nadya Dwinna Putri (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2024)
This research aims to analyze customer perceptions regarding the use of microcredit financing with a focus on the case study of Bank Syariah Indonesia (BSI) KCP Medan Kampung Baru. Utilizing surveys and qualitative data analysis, the research methodology aims to understand the strengths and weaknesses of the sample through observation, interviews and document analysis of the sample's perceptions of the product using Murabahah principles. In this context, research examines the factors that influence public trust in the progress, transparency and quality of the implementation of Murabahah law. The survey collected customer responses from BSI KCP Medan Kampung Baru, while qualitative data analysis was carried out to identify customer views in more detail. It is hoped that the findings of this research will help in understanding the effectiveness of implementing the Murabahah model in micro product development and how it affects customer needs and expectations. The practical implications of this can help Islamic banks improve their products and services and strengthen their ties with customers, especially at BSI KCP Medan Kampung Baru.